Prevalence of Sleep Disorders and their Effects on Sleep Quality in Epileptic Patients - Zohreh Yazdi; Khosro Sadeghniiat-Haghighi; Shoaib Naimian; Mohammad Ali Zohal; Mostafa Ghaniri (Basic and Clinical Neuroscience, 2013)
Introduction: Epilepsy is a complex pervasive neurobehavioral and social condition accompanied by a wide range of comorbid conditions that can adversely affect the quality of life of patients. Sleep complaints are common among patients with epilepsy. The aim of this study was to assess the prevalence of subjective sleep disturbances and its effects on sleep quality in epileptic patients.